Poem - Text and/or Image: Louise Dupre and Anouk Van Renterghem - Rozlozsnikova, Hana (Romanica Olomucensia, 2020)
The collection Carnet Ocre by Louise Dupre, a poet, novelist, and playwright from Quebec, and Anouk Van Renterghem, an artist from Brussels, approaches the intimate meditation of the personal experience of the quest for the poetic and creative voice emerging and radiating from the heart of the ``Earth-ocher'' because, as Louise Dupre states in the dedication: ``we are Earthlings and we love the Earth, which gives us life''. This collection succeeds in meeting the challenge of playing the score of the emotion of the encounter in the textual and graphic universe. Each poem is accompanied by a dry pastel that communicates directly to the text beside it by answering and supplementing it. What interests us in this versatile universe is the artistic strategies ensuring the correspondences, the analogies, and the union of these two main components - text and image, the whole of which forms the basis of the texto-scriptural imaginary. As for the way in which the ``poems-pastels'' of Louise Dupre and Anouk Van Renterghem are analysed, the focus on them of this paper will be from a thematic/symbolic point of view (cf. the instance of the imagination) by relying on semantic analytical (cf. mediation theory), musical (cf. prosodic harmony), and artistic (cf. chromatic circle theory, additive and subtractive theory) tools. This extension has helped to understand the evolution of the poetics and mediations that constitute the universe of the imaginary - the dynamic Earth poetics that come from the creation. The Imagination under study translates the process of birth, affirmation, and rebirth of the great voice of the lyrical subject
Keywords: poem; imaginary; imagination; pastels; mediation